Prevention of hepatitis C recurrence by bridging sofosbuvir/ribavirin from pre‐ to post‐liver transplant: a real‐life strategy. (26th December 2016) - Donato, Maria Francesca; Morelli, Cristina; Romagnoli, Renato; Invernizzi, Federica; Mazzarelli, Chiara; Iemmolo, Rosa Maria; Montalbano, Marzia; Lenci, Ilaria; Bhoori, Sherrie; Pieri, Giulia; Berardi, Sonia; Caraceni, Paolo; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV) re‐infection following liver transplant (LT) is associated with reduced graft and patient survival. Before transplant, Sofosbuvir/Ribavirin (SOF/R) treatment prevents recurrent HCV in 96% of those patients achieving viral suppression for at least 4 weeks before transplant. We evaluated whether a bridging SOF‐regimen from pre‐ to post‐transplant is safe and effective to prevent HCV recurrence in those patients with less than 4 weeks of HCV‐RNA undetectability at the time of transplant. Methods: From July 2014 SOF/R was given in 233 waitlisted HCV cirrhotics with/without hepatocellular carcinoma (HCC) within an Italian Compassionate Program. One hundred patients were transplanted and 31 patients (31%) treated with SOF/R bridging therapy were studied. Results: Liver transplant indication in bridge subgroup was HCC in 22 and decompensated cirrhosis in 9. HCV‐genotype was 1/4 in 18 patients. SOF 400 mg/day and R (median dosage 800 mg/day) were given for a median of 35 days before LT. At transplant time, 19 patients were still HCV‐RNA positive (median HCV‐RNA 58 IU/mL). One recipient had a virological breakthrough at week 4 post‐transplant; one died, on treatment, 1‐month post‐transplant for sepsis and 29/31 achieved a 12‐week sustained virological response (94%). Acute cellular rejection occurred in three recipients. On September 2016, 30 recipients (97%) were alive with a median follow‐up of 18 months (range 13‐25). Conclusions: In patients with suboptimal virological response at LT, a bridging SOF/R regimen helps avoiding post‐transplant graft reinfection.